Students' Geopathic Stress: Its Influence on Their Work-Related Stress, Burnout and On-the-Job Training Performance - Convocar, Jeremias L. (JPAIR Multidisciplinary Research, 2014)
Geopathic stress is a natural phenomenon which affects certain places and can be damaging to human health. This study determined the extent of geopathic stress (GS) among 253 randomly selected fourth-year college students and its influence on their work-related stress, burnout, and on-thejob training (OJT) performance. Using descriptive-correlational method, the study utilized published on-line GS questionnaire, stress test, burnout inventory, and students’ final ratings in OJT. The extent of GS among graduating college students revealed that 13.83% had “few feelings” of GS, 32.81% had “some strong feelings” of GS, 39.13% had “substantial GS feelings”, and 14.23% were “experiencing” GS. They had “fair” work-related stress, “some strong” feelings of burnout and “outstanding” OJT performance. Significant differences were found in students’ burnout when grouped as to the level of GS. A positive and significant relationship was found between GS and burnout and among work-related stress and the OJT performance. However, a negative and significant relationship was found between burnout and OJT performance. Hence, GS is a major stressor that triggered burnout and eventually affects students’ OJT performance.
Keywords: Geopathic Stress; work stress; burnout; ojt performance; influence; Descriptive-Correlational Study; Iloilo; Career in cruise tourism; cruise industry; mixed method, Philippines